Analysis of Coastal Abrasion Rate and Sediment Fractions at Tiram Beach, West Sumatra - Fauzan Azmi; Rifardi Rifardi; Ilham Ilahi (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Tiram Beach, located in Padang Pariaman Regency, West Sumatra Province, is one of the coastal areas under environmental pressure from coastal abrasion. Abrasion leads to shoreline retreat and negative impacts on local socio-economic activities. This study aims to analyze the rate of coastal abrasion and sediment fractions at Tiram Beach over 20 years (2003–2023), and to identify the dominant sediment characteristics in the area. The research methods included analysis of Landsat satellite imagery (2003, 2013, and 2023). Results show that Tiram Beach has undergone consistent shoreline retreat, with abrasion rates ranging from 2.2 to 3.1 meters per year. The sediment is predominantly composed of coarse sand and gravel, classified as poorly sorted, with skewness values indicating a dominance of coarse particles in certain zones. Contributing factors to abrasion include high-energy waves from the Indian Ocean, strong coastal currents, and human activities such as tourism and coastal infrastructure development. In conclusion, coastal abrasion at Tiram Beach is significant and poses a threat to the sustainability of the coastal zone if left unmanaged. Mitigation measures such as the construction of coastal protection structures, rehabilitation of coastal vegetation, and integrated coastal spatial planning are recommended to reduce future impacts.